2019
DOI: 10.1177/0886260519880164
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence in Childhood and Post-Childhood: The Experiences of Young Men Who Have Sex With Men in Beirut

Abstract: Sexual violence has been found to have psychosocial and sexual ramifications for men who have sex with men (MSM) but has not been studied in the Middle East. We assessed the prevalence and correlates of experiences of child and post-child sexual violence among young MSM residing in Beirut, Lebanon. In total, 226 MSM, aged 18 to 29, were recruited with long-chain peer referrals and administered a survey that included questions on history of being pressured to have sex, as well as specific forms of sexual harass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Logistic regression analysis was used to examine correlates of child sex abuse and experiences of sexual violence postchildhood; 17.3% experienced sexualabuse as a child (below age 13), while 63.3% experienced any form of sexual violence post-childhood-furthermore, 48.7% had experienced being forced or pressured to have sex during their lifetime, including 32.3% prior to age 18. These findings reveal a high prevalence of sexual violence among MSM in Beirut, both in childhood and post-childhood (8) .…”
Section: Discussionmentioning
confidence: 66%
“…Logistic regression analysis was used to examine correlates of child sex abuse and experiences of sexual violence postchildhood; 17.3% experienced sexualabuse as a child (below age 13), while 63.3% experienced any form of sexual violence post-childhood-furthermore, 48.7% had experienced being forced or pressured to have sex during their lifetime, including 32.3% prior to age 18. These findings reveal a high prevalence of sexual violence among MSM in Beirut, both in childhood and post-childhood (8) .…”
Section: Discussionmentioning
confidence: 66%
“…9 31 35-39 41 50-64 Nine studies 19 43 65-71 conceptualised sexual harassment as physical, verbal and non-verbal acts; physical consisted of purposely bumping or hurting someone, acting indecently and inappropriate touching, verbal consisted of inappropriate sexual comments about body parts, telling sexual or dirty jokes and asking a favour for having sexual intercourse; and non-verbal consisted of displaying inappropriate pictures through email/social media, inappropriate eye contact. We excluded three studies that reported measuring sexual harassment, but measured sexual violence explicitly defined and measured as sexual violence or sexual abuse in the study with forced sex or rape [72][73][74] (see table 1). Many studies did not deploy a validated tool, but either used a direct question or a series of behavioural questions (see table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that almost 10% of nurses in Thai Hospitals experience sexual harassment [ 31 ]. Sexual harassment is mostly carried out by patients with mental disorders (50%) [ 32 ]. A patient committed sexual harassment because he had a history of drinking alcohol, a history of sexual violence, and a history of previous abuse [ 33 ].…”
Section: Discussionmentioning
confidence: 99%